The impact of tectonic movements resulting from the oil fields in the province of Basra on the topography of the Earth's surface - Jassim Salman , Dr. Salim (Basra studies journal, 2023)
Basra Governorate occupies the southern part of Mesopotamia, specifically in the semi-arid zone of Al-Zubair. This semi-range contains subsurface folds representing most of the oil fields in the governorate, the most famous of which are Rumaila, Zubair, Nahran Omar, Majnoon, Tuba and Ratawi al-Luhais fields. These oil fields were formed as a result of the interaction of three main causes: the alpine movement, the eruption of the base rocks, and the tectonics of the salts. Since these elements are still effective, the oil fields are in a state of synthetic growth, which makes them affect the topography of the surface of the earth in the province of Basra. This study showed the nature of the impact of these fields on the topography of the Earth's surface.